2008
DOI: 10.1093/carcin/bgm237
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of dibenzo[a,l]pyrene transplacental carcinogenesis in mice born to mothers administered green tea: primary role of caffeine

Abstract: Our laboratory recently developed a mouse model of transplacental induction of lymphoma, lung and liver cancer by the polycyclic aromatic hydrocarbon, dibenzo[a,l]pyrene (DBP). Pregnant B6129SF1 females, bred to 129S1/SvIm males, were treated on day 17 of gestation with an oral dose of 15 mg/kg DBP. Beginning on day 0 of gestation, dams were given (ad lib) buffered water, 0.5% green tea, 0.5% decaffeinated green tea, caffeine or epigallocatechin-3-gallate (EGCG) (both at equivalent concentrations found in tea)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 49 publications
5
41
0
Order By: Relevance
“…CYP1B1 has been found to be, at least in part, under epigenetic control (43,44) and it has been suggested that CYP1B1 would make an excellent target for prevention strategies (45). In our previous studies, we showed that the addition of indole-3-carbinol, green tea, or caffeine to the maternal diet during pregnancy and nursing significantly reduced lung cancer multiplicity in 10-month-old offspring from mothers treated with 15 mg/kg DBP (9,10). The results presented in this study provide further evidence that Fig.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…CYP1B1 has been found to be, at least in part, under epigenetic control (43,44) and it has been suggested that CYP1B1 would make an excellent target for prevention strategies (45). In our previous studies, we showed that the addition of indole-3-carbinol, green tea, or caffeine to the maternal diet during pregnancy and nursing significantly reduced lung cancer multiplicity in 10-month-old offspring from mothers treated with 15 mg/kg DBP (9,10). The results presented in this study provide further evidence that Fig.…”
Section: Discussionsupporting
confidence: 79%
“…A classification scheme (40) devised under the direction of the Mouse Models of Human Cancers Consortium has been published and can be used for comparison with the WHO classification of lymphomas (39). We have, for the first time in any animal model, documented that exposure of pregnant mice to a single dose of a potent PAH, DBP, results in a very aggressive T-cell lymphoma in the offspring beginning at 10 weeks of age (8)(9)(10). Our hypothesis is that maternal transfer to the fetus results in cyp1b1-dependent bioactivation to DBP-(−)-anti-(11R,12S,13S,14R)-dihydrodiol epoxide and other reactive metabolites of DBP in the thymus producing a number of DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, B6129SF1/J mice possess an AhR-responsive allele, which makes these mice prone to carcinogenesis induced by PAHs via induction of Cyp1b1 and/or Cyp1a1 (Yu et al, 2006a). Furthermore, the mouse Cyp1b1 protein has the highest activity toward conversion of DBC to the carcinogenic fjord region diol-epoxide (Castro et al, 2008c; Luch et al, 1998). Dams were fed AIN93G (Harlan-Teklad, Madison, WI) during pregnancy and lactation.…”
Section: Methodsmentioning
confidence: 99%